การสังเคราะห์และศึกษาความคงตัวทางเคมีของสารเคอร์คูมินไดเอทิลไดกลูตาเรต - สุชาดา แสงวิมาน (จุฬาลงกรณ์มหาวิทยาลัย, 2017)
Curcumin is a polyphenolic compound found in turmeric (Curcuma longa L.). It has beendemonstrated for numerous pharmacological activities with a safety profile. However, the use ofcurcumin in clinical applications is still limited due to the extensive metabolism via phase Ilconjugation, resulting in low oral bioavailability. In this study, curcumnin diethyl diglutarate (CDG), a new curcumin prodrug, has been designed and synthesized. The chemical stability of CDG inphosphate buffer pH 7:4 and human plasma was tested. The results show that CDG can besynthesized by an esterification of both phenolic groups of curcumin with glutaric acid monoethylester chloride with the yield of 50.5%. The synthesized CDG was characterized by H and 13C nuclear magnetic resonance spectroscopy, infrared spectroscopy, high resolution mass spectrometry and melting point determination. The chemical stability of CDG was investigated by measuring the decrease of CDG in phosphate buffer pH 7.4 with ultra-high performance liquid chromatography. The initial degradation rate constant (kobs) and half-life (t1/2) was calculated using a pseudo-first order kinetic model. It was found that the kabs and tur of CDG were 2.48 x 10-2 min-1 and 27.9 min, respectively, while the kobs and t1/2 of curcumin were 2.39 x 10-2 min-1 and 29.0 min, respectively. The release of curcumin in human plasma from CDG was also studied by monitoring the reduction of CDG and occurrence of curcumnin. It was found that CDG degraded in human plasma with the kobs and tvz of 5.88 x 10-2 min-1 and 11.8 min respectively. The higher degradation rate in human plasma of CDG in comparison with that of phosphate buffer pH 7.4 indicates that the conversion of CDG to curcumin is accelerated. It implies that CDG undergoes hydrolysis reactions catalyzed by plasma esterases. In conclusion, this research shows that CDG has a potential to be developed as a curcumin prodrug with promising biological activities.